Road to Nicaea I (325): A Historical Overview - Thonippara, Francis (Asian Horizons, 2025)
As the article’s title indicates, an attempt is made to explain the immediate historical background of the Council of Nicaea I. The encounter of the Christian religion with the Jewish religion and the Greco-Roman world resulted in various efforts to explain the uniqueness of Christ. Maintaining monotheism and developing the Christian concept of the Trinity was not an easy task for the theologians of the early Church. The Jewish influence and the liberal use of Greek philosophy resulted in various heresies, including Arianism. Emperor Constantine, acting as the representative of God, convoked the first ecumenical council, Nicaea I, in 325. Unity of the Empire was the major concern of the Emperor, and the identification of the Church with the State was inaugurated with this Council. Besides, the functioning of the Council was modelled after the Roman Senate. The clear articulation of the Christian Creed is the greatest achievement of the Council, which is being recited even today with certain additions.